The literary fairy-tale by S. Nėris in Lithuanian children’s poetry - Linkevičius, Jonas (Literatūra, 1969)
The article gives a short survey dealing with the evolution of the rhymed fairy-tale in Lithuanian literature. The analysis is in its greater part devoted to „The Orphan" and „Eglė Queen of Grasssnakes", literary fairy-tales, by S. Nėris. It also analyses the evolution and peculiarities of literary fairy-tales previously never dealt with in terms of children’s poetry. This article points out that literary fairy-tales had no distinct traditions in Lithuanian children’s poetry before S. Nėris. Our poetess managed to enrich this literary genre with significant problems, brought it nearer to the children’s world, and reached a higher artistic level. This was due to the originality of character, image and poetics. Close attention is paid to such features in „Eglė Queen of Grasssnakes" that have not been studied before: national colour in literary fairy-tales, dramatic development of moral conflicts, composition matching the psychology of children, diversity of intonation, a harmonious combination of fantasy and reality (as seen by children). Literary fairy-tales by S. Nėris are often called folklore poems, fairy-tale poems. The author of the article suggests a more precise term, i. e. literary fairy-tale.